Technical appendix: The DeepTree layout and rendering engine - Block, Florian; Horn, Michael S.; Phillips, Brenda Caldwell; Diamond, Judy; Evans, E. Margaret; Shen, Chia (2012)
This technical report provides details regarding the DeepTree layout and rendering engine